Una aproximación a la publicidad cómplice actual: cuando las celebrities dejan de alabar - Fabián Centocchi, Claudio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
Two styles have usually been differentiated in the contemporary discourse of advertising (but only superficially as yet): «classic» advertising and «postmodern» advertising. Taking into account such interstylistic confrontation, this paper intends to describe a series of enunciative strategies that are implemented in TV commercials including celebrities. In fact, this corpus has been selected because we are interested in analyzing how the complementary enunciative link based on the «model of exemplification», which is typical of this kind of discourse, tends to become symmetrical in texts corresponding to the «postmodern» variant. We have focused on distinguishing some signifying operations which are part of the most innovative advertising.